SECONDARY SJOGREN’S SYNDROME IN PATIENTS WITH RHEUMATOID ARTHRITIS - Filip Guchev; Damjanovska Krstikj, Ljubinka; Bozhinovski, Georgi; Snezhana Perchinkova-Mishevska; Natali Jordanovska-Gucheva (Институт за јавно здравје на Република Северна Македонија, 2022)
Secondary Sjogren’s syndrome (sSS) is a connective tissue disease characterized by xeropthalmia and xerostomia, associated with another autoimmune disease. The prevalence of sSS in patients with rheumatoid arthritis (RA) is different in different countries, but is assumed at 10% of all RA patients and 20% of these have sub-clinical manifestations. This is a large subpopulation of patients with RA, especially taking into account that the clinical implications of their coexistence are not well explored. Aims: To analyze the effects of sSS on RA, the association between this syndrome and disease activity and disease evolution, presence of serological and immunological markers, disease duration and quality of life in patients with RA. Material and methods: We examined 42 patients, at the age of 18 to 70 years, diagnosed according to the criteria for classification and diagnosis by EULAR (2010). Twenty patients were diagnosed with RA and sSS, and 22 patients with RA without sSS. The groups were comparable regarding age, sex and disease duration. We analyzed the incidence of sSS, association with age, sex, demographic data, disease duration, extraarticular manifestations, and serologic tests (positive RF, anti-CCP) were also made. Disease activity was assessed by disease activity score (DAS28) and quality of life by the health assessment questionnairedisability index (HAQ-DI). The number of tender and swollen joints was assessed, as well as pain level by using the visual analogue scale (VAS), sedimentation rate (ESR), CRP, and immunological tests (SSA, SSB, antidsDNA, ANA, antiU1snRNP) were also made. Results: In the analyzed patients there was no statistically significant difference in ESR, CRP, DAS28, HAQ-DI, seropositivity of RF and anti-CCP and the presence of antidsDNA, ANA or antiU1snRNP and disease duration. Patients in the RA group had more tender, swollen joints and VAS. There was a statistically significant difference in SSA and SSB levels. There was no significant difference in the treatment of patients from both groups. Conclusion: There was no statistically significant difference in the level of disease activity and quality of life in patients with RA compared to sSS group.
Секундарен Сјегрен синдром кај пациенти со ревматоиден артритис
Keywords: Sjogren’s syndrome; rheumatoid arthritis; disease activity